Biomimicry Kinetic Facade as Renewable Energy - Bram Michael Wayne; Danny Santoso Mintorogo; Lilianny Sigit Arifin (Advances in Civil Engineering and Sustainable Architecture, 2019)
This article is an alternative research design for sustainable energy in high rise building through wind kinetic facade. This research purpose is to open the mindset of sustainable energy and to seek an alternative design for renewable energy facade through the wind while rising the diversity of building environments by sound in its process. In the modern city, the existence of energy is crucial and energy consumption demand is rising through time. The mindset of renewable energy facade through wind is purposely to support energy consumption. And the absolute existence of wind makes it possible to harvest energy through the day without restrictions, especially in high rise buildings. Sustainable energy is about how a building capable to create energy, reduce energy consumption, and creating environment diversity for human health and well-beingness. The environment elements that perfectly match with renewable energy facade through wind is sound.